Birth Metaphors: The Sculpture Crowning: a Contemporary Translation of the Nicene Creed - Bruckner, Isabella (Interdisciplinary journal for religion and transformation in contemporary society, 2025)
This article explores the theological and dogmatic significance of Crowning, a controversial sculpture by Esther Strauß depicting the Virgin Mary in the act of childbirth. The work was part of the DonnaStage exhibition commemorating the 100th anniversary of the Linz Cathedral and drew public attention following its vandalism in July 2024. Interpreting the sculpture as a visual exegesis of the Incarnation and the Nicene Creed, the article argues that Crowning functions as a contemporary theological statement on the power of generativity - both biologically and spiritually. Through a threefold inquiry - into the Christological doctrine of the double generation of the Son, the soteriological reading of resurrection as rebirth, and the iconological legitimacy of representing and participating in the divine generativity - the article situates Crowning within the broader tradition of Christian theological aesthetics. It concludes by considering how a "natally oriented" interpretation of dogma might reshape contemporary perspectives on faith, the Church, and societal transformation.